2013
DOI: 10.1186/cc11932
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of thymosin alpha 1 for severe sepsis (ETASS): a multicenter, single-blind, randomized and controlled trial

Abstract: IntroductionSevere sepsis is associated with a high mortality rate despite implementation of guideline recommendations. Adjunctive treatment may be efficient and require further investigation. In light of the crucial role of immunologic derangement in severe sepsis, thymosin alpha 1 (Tα1) is considered as a promising beneficial immunomodulatory drug. The trial is to evaluate whether Tα1 improves 28-day all-cause mortality rates and immunofunction in patients with severe sepsis.MethodsWe performed a multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…A lower expression and especially failure of restoration of HLA-DR expression appear indicative of immunoparalysis, as it is related to the susceptibility to opportunistic infections and outcome in sepsis patients [15]. Several promising immuno-adjuvant agents are slated for testing in the near future, including GM-CSF (ClinicalTrials.gov identifier: NCT02361528), IL-7, anti-PD-L1 (ClinicalTrials.gov identifier: NCT02576457), and thymosin-alpha-1 [2,8,12,13,16,17]. Given the remarkable success of immunotherapy in cancer and the similarities in the immune defects in cancer and sepsis patients [18], it appears plausible that immunotherapy may represent a major advance in the treatment of this highly lethal disease.…”
Section: How Should Development Of Immunosuppression Impact Clinical mentioning
confidence: 99%
“…A lower expression and especially failure of restoration of HLA-DR expression appear indicative of immunoparalysis, as it is related to the susceptibility to opportunistic infections and outcome in sepsis patients [15]. Several promising immuno-adjuvant agents are slated for testing in the near future, including GM-CSF (ClinicalTrials.gov identifier: NCT02361528), IL-7, anti-PD-L1 (ClinicalTrials.gov identifier: NCT02576457), and thymosin-alpha-1 [2,8,12,13,16,17]. Given the remarkable success of immunotherapy in cancer and the similarities in the immune defects in cancer and sepsis patients [18], it appears plausible that immunotherapy may represent a major advance in the treatment of this highly lethal disease.…”
Section: How Should Development Of Immunosuppression Impact Clinical mentioning
confidence: 99%
“…However, due to the lack of early triage of sepsis system, limited ICU resources, and low-to-high level hospital medical visiting system, many septic patients might lose the precious period when they could receive the intensive care management (5,16). The efficacy of thymosin alpha 1 for severe sepsis (ETASS) study conducted in Guangdong province, an economically developed region in mainland China, reported that the median time when the patient developed first organ failure and enrollment was 28 and 42 h, respectively in the control and treatment groups (17). While the data from our sepsis database represents the economically less developed area, more than 60% of the severe sepsis patients developed organ failure after more than 48 h upon ICU admission.…”
Section: Mortality Of Sepsismentioning
confidence: 99%
“…The duration of treatment ranges from 6 to 10 days and the total dose ranges from 9.6 to 22.4mg. Four trials reported thymosin α1 alone (17,(23)(24)(25), and the remaining six trials reported thymosin α1 combination with ulinastatin (18)(19)(20)(21)(22) (19,21), and three reported interleukin-6 (19,21,22).…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Overall, six trials were categorized as at low risk of bias (17)(18)(19)(20)24), and four as at unclear risk of bias (21)(22)(23)25). Adequate randomized sequence generated in seven trials (17-20, 24, 25), and appropriate allocation concealment were reported in six trials (17)(18)(19)(20)24). Blinding of outcome assessments was unclear or seldom reported in these trials, but the primary outcome (i.e., 28-day mortality) was less prone to be influenced by lack of blinding.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation